A fenntartói irányítás jogszabályi keretei a felsőoktatási intézmények vonatkozásában - Bárány V., Fanni (Kultúratudományi Szemle, 2022)
Legislative framework of maintenance management for higher education institutions Fanny V. Bárány This study focuses on examining the operation of Hungarian higher education institutions from the perspective of maintenance management. In order to understand the changes in the management of maintaining, it is essential to know the regulations that have already been repealed. Therefore, in my study, in addition to the current regulations, I also examine the previous legal environment. As a result of the study, it has been established that the state has a wide range of regulatory, operational, control and financing tasks in connection with the operation of state and, in part, non-state higher education institutions and the entire higher education system.